Contribution of Tourism Industry in Nepal: Measuring Its Economic Impact - Kharel, Khom Raj; Kharel, Suman (Patan Pragya, 2021)
This research paper is concern with the economic impact of tourism industry in Nepalese economy. Tourism industry is multi-industry and multi-product and tourist demand is complementary and has to be met by a number of goods and services, which are not only spatially disparate but also functionally different. The tourist product is of a highly perishable nature and the bulk of tourist facilities have an in-built inflexibility. It initially reviews the concert and using a model, it deals with the factors affecting the economic impacts associate with tourism. The economic impact is measured in terms of direct employment, foreign exchange earnings, GDP and government royalty due to the flow of total tourists arrival of tourists in different fiscal years by using linear regression model and correlation. Results reveal that there is positive economic impact of tourism industry in Nepalese economy.